기증각막 관련 미생물학적 검사 결과 분석 - 정일(Il Jung); 고병이(Byung Yi Ko) (Daihan angwa haghoi jabji, 2022)
목적: 기증각막과 관련해 시행한 미생물학적 검사에서 동정된 미생물 및 임상적 중요성에 대해 알아보고자 하였다. 대상과 방법: 본 병원에서 2008년 10월부터 2020년 12월까지 각막이식을 받은 환자 중 기증각막 관련 미생물학적 검사를 시행한 94명 114안을 대상으로 의무기록을 후향적으로 분석하였다. 각막이식 수술 중 공여자의 각공막 테두리와 보존액인 OptisolTM-GS (Bausch & Lomb, Rochester, NY, USA)를 대상으로 미생물학적 검사를 하였고, 배양에서 동정된 세균에 대한 항생제 감수성 검사를 시행하였다. 결과: 미생물 검사에서 균이 동정된 경우는 모두 국내 기증각막이었고, 수입한 각막에서는 검출되지 않았다. 각공막 테두리에서 그람음성 간균이 발견된 환자가 3안(2.6%)이고, 그중 배양 검사에서 Acinetobacter baumanii/hemolyticus가 2예, Pseudomonas aeruginosa가 1예가 동정되었다. 각공막 테두리에서는 균이 검출되지 않고 보존액에서만 Acinetobacter baumanii/hemolyticus가 동정된 1안이 있었다(0.9%). 항생제 감수성 검사에서 Colistin 이외의 다른 항균제에 다약제 내성을 가지고 있었다. 균이 발견된 모든 증례에서 각막이식 수술 후 각막염이나 안내염은 발생하지 않았다. 결론: 각막이식술 시 사용하는 기증각막 또는 보존액에서 드물지만 균이 동정되는 경우가 있으므로 기증각막을 다루는 모든 과정에서 오염에 주의하여야 하겠다. 각막이식 수술 시 사용하는 경험적 항생제는 다약제 내성균을 억제하기에 충분한 항균력을 가지는 약제를 선택하여야 한다. Purpose: This study analyzed the microorganisms identified in donor corneas and their clinical significance. Methods: The medical records of 94 patients (114 eyes) who underwent keratoplasty and microbiological tests of the donor corneas from October 2008 to December 2020 at our hospital were reviewed retrospectively. During keratoplasty, we conducted microbiological tests of the corneoscleral rim of the donor cornea and preserving solution Optisol™-GS (Bausch & Lomb, Rochester, NY, USA), and examined the antibiotic susceptibility of bacterial isolates from the cultures. Results: Some isolates of domestic donor corneas revealed bacteria, but none of the imported corneas did. Gram-negative bacilli were detected from the corneoscleral rim in three eyes (2.6%): two cases of Acinetobacter baumannii/haemolyticus and one case of Pseudomonas aeruginosa. In one case (0.9%), Acinetobacter baumannii/haemolyticus was identified from preserving solution, with no bacteria found in the corneoscleral rim. Antibiotic susceptibility tests showed multi-drug resistance, except to colistin. In all cases where bacteria were detected, there was no keratitis or endophthalmitis after corneal transplantation. Conclusions: Although rare, bacteria can be identified from donor corneas or the preserving solution used in corneal transplantation. Therefore, caution is needed in all processes dealing with donor corneas. Empirical antibiotics that have sufficient antimicrobial activity to suppress multi-drug resistant bacteria should be selected in corneal transplantation. KCI Citation Count: 0